High-Temperature (940 °C) furnace in 18/20 T cold bore magnet. (January 2018) - Wang, Ze; Hou, Yubin; Feng, Qiyuan; Dong, Hongliang; Lu, Qingyou
Highlights: A 940 °C furnace which can works in 52 mm cold bore magnet is manufactured. With a LN2 jacket absorbing the radiation, long-time running is achieved. A compact heating structure permits 30 samples to be treated at the same time. Theoretically, the furnace structure improves space utilization rate. Abstract: We present a high-temperature furnace that can work continuously in an 18/20 T cold bore magnet. A specially designed liquid nitrogen (LN2 ) jacket is between the high-temperature parts of the furnace and the liquid helium in the magnet Dewar. With LN2 serving as the cooling medium, the calculated value of radiation received by the liquid helium (LHe) is as low as 0.004 W. The furnace can be put into LHe Dewar directly. Together with the magnet, the furnace can provide experimental conditions of a strong static magnetic field and temperatures up to 940 °C. A cobalt oxide synthesis in solution was carried out at 200 °C with and without a 15 T magnetic field for 8 h. Differences in material structure with the applied field were observed in transmission electron micrographs of the products. A Co film sample was treated at 900 °C with and without a 6.8 T magnetic field for 30 min. The scanning electron micrographs of the treated samples show that magnetic field had a clear effect on the heat treatment process. These two applications confirmed the performance of the furnace both in high magnetic field and at high temperature.